Pengaruh Penerapan Blended Learning Terhadap Motivasi Belajar Siswa di SMA N 1 Salimpaung - Peggy Reflia Utami; Rani Sofya (Universitas Negeri Padang, 2022)
This study aims to: 1) analyze the differences in student learning motivation using the blended learning method and students who do not use the blended learning method, 2) analyze the differences in student motivation before and after the application of the blended learning method. This type of research is a quasi-experimental. The population of this research is all students of class XI SMA N 1 Salimpaung which is divided into two majors, namely science and social studies. The research sample was 58 students which were divided into 29 students in the control group and 29 students in the experimental group. The data collection technique was in the form of a questionnaire given before and after treatment. The data obtained were analyzed and tested with the Mann-Whitney U test and paired sample t-test. Using SPSS version 20. The results show that 1) there is a significant difference between the learning motivation of students who use the blended learning method and students who do not use the blended learning method, 2) there are differences in the average learning motivation of students before and after the application of the blended learning method.Keywords : learning motivation1, blended learning2 , quasi experiment3